KINERJA MEDIA PEMBAWA UNTUK SURFAKTAN MES DARI MINYAK SAWIT UNTUK PENERAPANNYA PADA OIL WELL BORE CLEANING - Fitria Riany Eris, Erliza Hambali, Ani Suryani, Pudji Permadi (Jurnal Teknologi Industri Pertanian, 2016)
Well productivity can be significantly affected by the number of skin in the wellbore area. One of thealternative ways to solve the problem is oil well bore cleaning application by using methyl ester sulfonate (MES)surfactant. Surfactants need a carrying medium and in this study the utilization of diesel and biodiesel as acarrier was assessed. Surfactant was formulated with NaCl and aromatic solvents and its effect on interfacialtension (IFT), thermal stability, phase behaviour, and wettability alterationwere measured. The best oil-basedsurfactant solution was obtained from the formulation of 5% MES surfactant with 5% xylene inclusion tobiodiesel as the carrying medium. This solution was then injected into an injection water which was alreadyadded in with 1% NaCl. It was found that biodiesel could be used as a substitute for diesel as a carryingmedium in oil wellbore cleaning activity on well X as the resulted surfactant solution was able to maintain IFTvalues until day seven, form microemulsion with an IFT value of 1.12x10-2 dyne/cm, and alter wettability of rockstoward water-wet.Keywords: palm oil, surfactant, MES, oil well bore cleaning